Acinetobacter baumannii Secretes a Bioactive Lipid That Triggers Inflammatory Signaling and Cell Death - Tiku, Varnesh; Kew, Chun; Kofoed, Eric M.; Peng, Yutian; Dikic, Ivan; Tan, Man-Wah (Frontiers in Microbiology, 2022)
Acinetobacter baumannii is a highly pathogenic Gram-negative bacterium that causes severe infections with very high fatality rates. A. baumannii infection triggers innate as well as adaptive immunity, however our understanding of the inflammatory factors secreted by A. baumannii that alarm the immune system remains limited. In this study, we report that the lab adapted and clinical strains of A. baumannii secrete an inflammatory bioactive factor which activates TLR2, leading to canonical IRAK4-dependent NF-κB signaling and production of pro-inflammatory cytokines interleukin (IL)-6 and IL-8 and activation of the inflammasome pathway causing pyroptotic cell death. Biochemical fractionation of the A. baumannii culture filtrate revealed the hydrophobic nature of the inflammatory factor. Concordantly, lipase treatment of the culture filtrate or TLR2 inhibition in macrophages abrogated NF-κB activation and cell death induction. Culture filtrates from the LPS- and lipoprotein-deficient A. baumannii mutants retain immuno-stimulatory properties suggesting that a lipid other than these known stimulatory molecules can trigger inflammation during A. baumannii infection. Our results reveal that A. baumannii secretes a previously unappreciated inflammatory bioactive lipid that activates multiple pro-inflammatory signaling pathways and induces cell death in human and murine macrophages.